Planning for diversity : policy and planning in a world of difference - Reeves, Dory, 1957- (Routledge, 2005)
The practical importance of diversity and equality for spatial planning and sustainable development is still not widely understood. Using international examples, this book shows planners and educationalists the benefits of building in a consideration of diversity and equality at each stage and level of planning. Despite being one of the most diverse and gender balanced of the built environment professions, complacency has been widespread in planning. This book shows why a diverse profession is important and drawing on a wide range of good practice, shows how those involved in planning can devel.
Keywords: City planning -- Social aspects.; Sustainable development.; Social justice.; Multiculturalism.; Cultural pluralism.; Social Justice; Cultural Diversity; Développement durable.; Justice sociale.; Multiculturalisme.; Diversité culturelle.; sustainable development.; multiculturalism.; POLITICAL SCIENCE -- Public Policy -- Regional Planning.; City planning -- Social aspects; Cultural pluralism; Multiculturalism; Social justice; Sustainable development